Diseño de un sistema de costos en la asociación artesanal de producción agrícola y pecuaria (a.p.a.p) la chacrita, ubicada en la comunidad Cumbijin, perteneciente al Cantón Salcedo, Provincia de Cotopaxi - Paula Toaquiza, Sonia Mariela (2019)
It is essential that the Artisanal Association of Agricultural and Livestock Production (A.P.A.P) "LA CHACRITA" has a cost system for the best decision making in the administrative and financial issues. This research aims to design a system of costs per process to correct the poor control of accounting records, especially the determination of cost elements and thus have better management of the economic resources of the association. In order to fulfill this purpose, methods such as bibliographic and documentary compilation were used; techniques such as the application of interviews to the person in charge of the production department and the observation guide were carried out directly in the Association with the objective of collecting primary information for the achievement of the cost system. Through the situational diagnosis, a clearer idea of the problem in question was obtained. Also, the competencies related to the professional field and the scientific and technical foundation are described, the same ones that contributed to the achievement of the present project. At the end of the project, it was determined that the current price obtained in the sale of the product, only covers the payment of the raw material and the difference for direct labor and in some cases, no profit is generated, due to the empirically how the costs are determined. As a result of the research work, it is proposed to increase all the costs involved in the elaboration of a technical way to an average sale price of $ 2.51 per cheese, obtaining an ideal profit of $ 0.58 equivalent to 30% per cheese, whose percentage means an increase in income and therefore in profit.